Efficacy of Jatyadi Taila Uttarbasti in the Management of Urethral Stricture a Single Case Study - Varsadiya, Dr.Akash; Sharma, Dr.Rajeshkumar; Kanani, Dr. Dipa (Asian Journal of Pharmaceutical Research and Development, 2024)
In Ayurveda, Acharya Sushrut mentioned an excellent treatment named Uttarbasti for urethral stricture known as Mutrakruccha in classical scriptures. Mutrakruccha translates to difficulty in micturition. It can be associated with urethral stricture due to the similarity of symptoms. Urethral stricture disease is often seen in patients with recurrent urinary tract infections, urethral injuries, or post-surgical procedures conducted through the urethra. The most common causes of urethral stricture today are traumatic or iatrogenic. Inflammatory or infectious, malignant, and congenital aetiologies are less common. There is a low success rate of Western medical science treatment for urethral stricture disease. Surgical treatment of urethral stricture disease is indicated when the patient has severe voiding symptoms, bladder calculi, increased postvoid residual, urinary tract infection, or when conservative management fails. Urinary tract infections (UTIs) should be adequately treated before surgical intervention. In this case study, a 39-year-old male patient complained of suffering from symptoms like the strangury of urine, pain during micturition, the flow of urine is very poor, frequent micturition and occasionally burning micturition. After clinical examination and radiological testing, the patient was identified as having urethral stricture and treated with Jatyadi Taila Uttarbasti for 21 days at Shalyatantra OPD, Government Akhandanand Ayurved College and Hospital, Ahmedabad. After completion of treatment, the patient felt 75% relief in symptoms. So, we can conclude that non-invasive treatment such as Uttarbasti is highly advisable in patients having Urethral stricture.